2018
DOI: 10.3390/molecules23020450
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Allergic Contact Dermatitis and Atopic Dermatitis-Like Skin in BALB/c Mouse through Oral Administration of Fermented Barks of Alnus sibirica

Abstract: Phytochemical isolation of fermented Alnus sibirica (FAS) which was produced by using Lactobacillus plantarum subsp. argentoratensis, exhibited multiple and different composition compared with the original plant. Anti-allergic contact dermatitis (anti-ACD)/anti-atopic dermatitis (anti-AD) activities (visual observation and regulation of Th1/Th2 cytokines and IgE in blood) of FAS and the barks of Alnus sibirica extract (AS) and the two diarylheptanoids, hirsutenone (1) and muricarpon B (2), which are major comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…From our previous study, 17 compounds from fermented AS (FAS) were isolated and evaluated for their antioxidant, anti-inflammatory, and anti-atopic dermatitis activities, in vitro and in vivo, including the quantitative analysis of its components [23,24,25]. The present paper describes the evaluation of antioxidant and anti-inflammatory effects on the enzymatic hydrolysis (EAS).…”
Section: Introductionmentioning
confidence: 99%
“…From our previous study, 17 compounds from fermented AS (FAS) were isolated and evaluated for their antioxidant, anti-inflammatory, and anti-atopic dermatitis activities, in vitro and in vivo, including the quantitative analysis of its components [23,24,25]. The present paper describes the evaluation of antioxidant and anti-inflammatory effects on the enzymatic hydrolysis (EAS).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that they have antioxidant, anti-inflammatory [58], anti-atopic dermatitis [63], and cytotoxic [64] properties. Lee et al [65] reported that the oral administration of fermented AS extracts (FAS) reduced the expression of IgE, IL-4, and IFN-γ in splenocytes from BALB/c mice with atopic-like dermatitis. However, they reported only the mitigating effects on systemic inflammation and did not describe the effects of AS extracts on the various cytokines associated with skin inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Allergic contact dermatitis (ACD), a chronic inflammatory skin disease, is a type IV delayed-hypersensitivity response induced by sensitization to allergens that causes redness, edema, and dryness of the skin [ 1 , 2 ]. Furthermore, the prevalence of ACD in children and adults worldwide is 15–20% and 1–3%, respectively [ 3 , 4 , 5 ]. The prevalence rate of ACD is higher in young children under 10 years than it is adults [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the prevalence of ACD in children and adults worldwide is 15–20% and 1–3%, respectively [ 3 , 4 , 5 ]. The prevalence rate of ACD is higher in young children under 10 years than it is adults [ 3 , 6 ]. Systemic corticosteroid or steroids combined with methotrexate, and azathioprine have been used for ACD [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation